(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ginting E, Utomo JS, Kuswantoro H, Han W-Y. Physicochemical characteristics of promising soybean lines adapted to acid soil and the tofu produced. Biodiversitas 22: 5012-5022. Breeding of soybean varieties adapted to different agro-ecological conditions in Indonesia is essential in terms of increasing domestic production through extensification. About 20 promising soybean lines adapted/tolerant to acid soil have been available, thus it is necessary to study their physical and chemical characteristics as well as the suitability as ingredients for tofu products. Four improved varieties (Grobogan, Tanggamus, Anjasmoro, and Wilis) were used as the checks. The results showed that one line belonged to large-seeded, namely Tgm/Anj-995 (15.13 g/100 seeds), slightly smaller than Grobogan (16.26 g/100 seeds). Eighteen lines were medium (similar to Anjasmoro and Tanggamus varieties), while one line was small-seeded (similar to Wilis variety). Five lines contained higher protein (40.35–41.80% dw) relative to four check varieties (36.03–38.18% dw). Tofu prepared from Tgm/Anj-908 and Tgm/Anj-991 lines had the highest scores for color, aroma, and taste acceptances; however, the texture was slightly firm, followed by the Tgm/Anj-932, Tgm/Anj-995, Tgm/Anj-862, and Tgm/Anj-888 lines, which had a softer texture. Their scores were slightly higher than those of Anjasmoro. This suggests that selected soybean promising lines tolerant to acid soil have better physical and nutritional performances relative to their check varieties, with six lines suitable for tofu ingredients.